ENERGY TRANSITION, LEGAL CERTAINTY, AND THE NEW ENVIRONMENTAL LICENSING FRAMEWORK: PERSPECTIVES FOR THE GREEN HYDROGEN AND AMMONIA INDUSTRY IN BRAZIL - Sá, Tadeu Dote; Santana, Givanildo Ximenes; Duarte, João Guilherme de Oliveira; Gomes, Rickardo Léo Ramos (Seven Editora, 2026)
The energy transition has redefined regulatory and economic priorities in the international scenario, especially with regard to the consolidation of new production chains linked to low-emission sources. In this context, the debate on Brazilian environmental licensing gains strategic relevance in light of the expansion of the green hydrogen and ammonia industry. The research was developed using a qualitative approach, and two research methods were applied: bibliographic research and documentary research. The general objective of this study is to analyze the impacts of the new Brazilian environmental licensing framework on legal certainty and the consolidation of the green hydrogen and ammonia industry within the context of the energy transition, identifying regulatory challenges and institutional opportunities for the sustainable development of the sector. It is concluded that the new environmental licensing framework, by seeking to provide greater predictability and rationality to administrative procedures, may directly influence legal certainty and the investment environment in the green hydrogen and ammonia sector. The consolidation of this industry in Brazil will depend on the institutional capacity to harmonize economic development, energy transition, and environmental protection, ensuring regulatory stability and trust as the basis for sustainable growth.